Large Deflection of Heated Orthotropic Cylindrical Shallow Shell - Biswas, Paritosh (Defence Science Journal, 2014)
This paper presents an analysis of large deflection of heated orthotropic shallow cylindrical shell. The governing differential equations have been derived on the basis of Berger's assumption and have been solved for a rectangular panel with simply-supported edges.